Information Technologies in Environmental Engineering ITEE 2007 - Third International ICSC Symposium - Marx Gómez, Jorge; Sonnenschein, Michael; Müller, Martin; Welsch, Heinz; Rautenstrauch, Claus (Environmental Engineering, 2007)
Potentially dangerous environmental changes are happening in the atm- phere, oceans, animal habitats and places where hazardous materials are used, or have been discarded without adequate environmental protections. These increasing problems that also affect human health demand for int- disciplinary approaches where engineers, natural scientists, economists and computer scientists work together. Information technology has become significant to all scientific groups and fields involved in environmental - gineering: Model based systems which enable the study of environmental changes have been developed and are being extended to manage those - vironments. New paradigms for designing objects to enable easy dis- sembly and recovery of components contribute to reuse. Web-based - formation systems enhance public awareness to environmental changes and allow participation in decision making. Developments in exploiting - ternative energy sources are reducing dependence on non-renewable - sources. Numerical economy-environment models contribute to co- benefit analysis of environmental policy, and environmental monitoring and accounting systems facilitate market-based environmental regulation. Further advance is only possible if scientific teams have adequate expe- ence, methods and tools for investigation of the changes in the envir- ment. Success requires a high level of organization related to technical as well as scientific and human aspects of information handling. This book publishes the results of the ITEE 2007 conference where information about the topics above has been presented and discussed among environmental engineers, computer scientists and economists. March 2007 Jorge Marx Gómez Michael Sonnenschein Martin Müller Heinz Welsch Claus Rautenstrauch VI Editors Prof. Dr.